SITUASI STRATEGI PROMOSI KESEHATAN DI VICO INDONESIA, TAHUN 2016 - Khansa Nadra (Universitas Airlangga, 2018)
This research is about health promotion strategy in Health department, VICO Indonesia in 2016. VICO or Virginia Company is an oil and gas company. The main office is located in Jakarta and for the production, VICO have four stations (field) that is located in East Kalimantan. This research will be spesifictly describe the health promotion strategy that have been done in Badak Field, Muara Badak, Kutai Kartanegara, East Kalimantan. The importance of strategy in health promotion is the reason why this research is done. Health promotion strategies are the means or steps needed to achieve or accelerate the health promotion goals. Ottawa Charter is basic of the health promotion strategy. The aim of this study is to describe the health promotion activities / programs in the Health department of VICO Indonesia, East Kalimantan 2016 based on five action means of Ottawa Charter. This research used a descriptive approach with data retrieval from observation, an interview, and supported by secondary data. VICO has a promotive and preventive section (promprev) inside the Health department, to take care of health promotion and prevention in VICO Indonesia. The results shows the activities that related to Ottawa Charter are the VICO president policy, facility compliance, education, socialization, inspection, training, as well as other activities related to health workers. The conclusion that can be drawn is the health promotion strategy at the VICO Indonesia Health department, East Kalimantan 2016, is up to standart with the five action means in Ottawa Charter   Keyword: Health Promotion, Ottawa Charter, VICO Indonesia